Charlie's Eye - "Horgan, Dorothy" (Puffin: London, 1998)
Charlie has never been bothered by the fact that she has a glass eye - indeed, her tricks make her a hero at school. But when Jason Jones joins her class, and calls her handicapped, she has to set out to prove him wrong.
Keywords: Children with disabilities